心脸皮肤综合症中的皮肤表现. (2nd January 2019) - Bessis, D.; Morice‐Picard, F.; Bourrat, E.; Abadie, C.; Aouinti, S.; Baumann, C.; Best, M.; Bursztejn, A.‐C.; Capri, Y.; Chiaverini, C.; Coubes, C.; Giuliano, F.; et al.
Abstract : Linked Article:  Bessis et al. Br J Dermatol 2019;180 :172–180